Improved tribological performance of TiAlSiN coated cemented carbide specimens via a pulsed magnetic field treatment - Zhang Lin; Long Haochen; Wu Mingxia; Yang Gang; Yang Yi; Liu Jian (MATEC Web of Conferences, 2024)
Pulsed magnetic field treatment, as a novel, quick and environmentally friendly post-processing approach can directly modify the coated tools without causing damage. This study examined the wear performance of the TiAlSiN-coated cemented carbide block specimens treated by the pulsed magnetic fields in both dry friction and cutting fluid friction. The findings show that TiAlSiN coating block specimens subjected to pulsed magnetic fields exhibit better wear resistance in both friction conditions. The wear rate of the coating decreases by 21.49% in a dry friction environment, and the friction process becomes more stable while the wear width of the coating decreases by 4.60% in the cutting fluid friction environment. In addition, the nano-indentation tests show that the hardness and elastic modulus of the coating increases by 6.58% and 5.64%, and the coating binding force increases by 15.27% after the treatment.